Etomidate Shows Prospect as an Anti-Arrhythmic Drug Conferring Safe Sedation and Sinus Conversion Simultaneously - Maryam Saif Al Ali; Anas Musa; Wael Hamadeh; Esam Seddik (Dubai Medical Journal)
This case is of a 76-year-old man with a known history of hypertension, type 2 diabetes mellitus, and ischemic heart disease, who presented to our department with chest pain and palpitations. His electrocardiogram showed a ventricular tachycardia (VT), but fortunately our patient was hemodynamically stable. A trial of adenosine was given to convert the patient’s heart back to sinus rhythm, but was unsuccessful and the rhythm remained as VT. Soon after, the patient suddenly became hemodynamically unstable as his blood pressure acutely declined; thus, the decision to perform a direct current cardioversion was taken. Bearing in mind that the patient was still awake, he was given 10 mg of intravenous etomidate as a pre-procedural sedative. During the time it took to prepare for the procedure, the patient’s rhythm reverted from VT to a regular sinus rhythm, raising his blood pressure back to normal and achieving hemodynamic stablility, negating the need of any electrical or chemical cardioversion. Our patient was then handed over to the cardiology team for an emergency percutaneous coronary intervention procedure and an implantable cardioverter-defibrillator procedure, both of which were successful. Etomidate was used in this case for the purpose of sedation, and as luck would have it, it seems that it had also incidentally reverted the arrhythmia back to normal.